1995
DOI: 10.1093/infdis/171.6.1683
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Cellular Immune Responses and Interferon-  Release after Long-Term Diethylcarbamazine Treatment of Patients with Human Lymphatic Filariasis

Abstract: Cellular immune responses to filarial antigens were examined in persons before and 1 year after beginning treatment with diethylcarbamazine (DEC). The subjects (17 microfilaremics, 13 asymptomatic amicrofilaremics, and 13 with elephantiasis) had not responded to Brgia malayi adult worm antigen (BmA) before chemotherapy. T cell proliferative responses to BmA improved significantly after therapy in the 3 clinical groups (P < .05) but was highest in the elephantiasis patients and asymptomatic amicrofilareimics. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
67
1
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 14 publications
4
67
1
1
Order By: Relevance
“…Similar results were obtained in Brugiainfected gerbils, where Mf þ gerbils are unable to produce IL-2 [31]. Moreover, ivermectin leads to a partial restoration of the suppressed Th1 responses in humans [13,32]. Several mechanisms may explain the induction of unresponsiveness by Mf.…”
mentioning
(Expert classified)
“…Similar results were obtained in Brugiainfected gerbils, where Mf þ gerbils are unable to produce IL-2 [31]. Moreover, ivermectin leads to a partial restoration of the suppressed Th1 responses in humans [13,32]. Several mechanisms may explain the induction of unresponsiveness by Mf.…”
mentioning
(Expert classified)
“…The fact that only live parasites can induce Foxp3 within the CD4 ϩ population is consistent with both field and laboratory data linking active infection to immune regulation. For example, in human studies, T cell responsiveness is regained after drug-induced parasite killing (11). Moreover, live L3 larvae have been shown to directly inhibit in vitro responses of human Langerhans cells (69) and peripheral blood lymphocytes (13).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the asymptomatic subjects, who carry high levels of circulating transmissionstage microfilariae, display a muted immunological response (5)(6)(7)(8), failing to mount parasite-specific T cell proliferative and cytokine responses. The degree of suppression is accentuated with higher parasite loads (9), and can be reversed by anti-filarial chemotherapy (10,11). Peripheral T cell populations in infected individuals show elevated expression of CTLA-4 and Foxp3, suggesting an increase in effector T cell anergy and regulatory T cell (Treg) 3 activity (12,13).…”
mentioning
confidence: 99%
“…Studies of Bancroftian filariasis in Haiti 11,12 and Malayan filariasis in Indonesia 13 have demonstrated increased T cell proliferation to parasite antigen at a variety of timepoints (3.9-12 months) following treatment with diethylcarbamazine (DEC) administered at a dose of 6 mg/kg/day or /week for 12 doses 11 or with ivermectin. 12 Of interest, PBMCs from a population in the Cook Islands infected with W. bancrofti displayed not only impaired cellular proliferation to Brugia malayi worm extract at baseline, but ongoing suppression of proliferation for up to two weeks following treatment with DEC. 14 Sartono and others 15 have shown that in addition to T cell proliferative responses, production of IFN-␥ in response to B. malayi crude adult antigen increased significantly one year after treatment in a study population in Indonesia, an area endemic for Brugian filariasis; however, patients in this study were treated with DEC every week for the entire year prior to reassessment of their cellular responsiveness. Diethylcarbamazine, in addition to its antifilarial activity, has measurable antifungal and antibacterial properties 16 and has been shown to exert an effect on the response to mf in vitro independent of the effector cell population.…”
mentioning
confidence: 64%